Postoperative Hypotension and Surgical Site Infections After Colorectal Surgery: A Retrospective Cohort Study. (November 2018) - Yilmaz, Huseyin O.; Babazade, Rovnat; Leung, Steve; Zimmerman, Nicole M.; Makarova, Natalya; Saasouh, Wael; Stocchi, Luca; Gorgun, Emre; Sessler, Daniel I.; Turan, Alparslan
Abstract : BACKGROUND: Hypotension compromises local tissue perfusion, thereby reducing tissue oxygenation. Hypotension might thus be expected to promote infection. Hypotension on surgical wards, while usually less severe than intraoperative hypotension, is common and often prolonged. In this retrospective cohort study, we tested the hypotheses that there is an association between surgical site infections and low postoperative time-weighted average mean arterial pressure and/or postoperative minimum mean arterial pressure. METHODS: We considered patients who had colorectal surgery lasting ≥1 hour at the Cleveland Clinic between 2009 and 2013. We defined blood pressure exposures as time-weighted average (primary) and minimum mean arterial pressure (secondary) within 72 hours after surgery. We assessed associations between continuous blood pressure exposures with a composite of deep and superficial surgical site infection using separate severity-weighted average relative effect generalized estimating equations models, each using an unstructured correlation structure and adjusting for potentially confounding variables. RESULTS: A total of 5896 patients were eligible for analysis. Time-weighted mean arterial pressure and surgical site infection were not significantly associated, with an estimated odds ratio (95% CI) of 1.03 (0.99–1.08) for a 5-mm Hg decrease ( P = .16). However, there was a significant inverse association between minimum postoperative mean arterial pressure and infection, with an estimated odds ratio of 1.08 (1.03–1.12) per 5-mm Hg decrease ( P = .001). CONCLUSIONS: Postoperative time-weighted mean arterial pressure was not associated with surgical site infection, but lowest postoperative mean arterial pressure was. Whether the relationship is causal remains to be determined.